The research in education in France: results of enquiries about research centres and periodicals - Beillerot , Jacky (Swiss Journal of Educational Research, 2000)
A national committee of research coordination in education created in 1995 by the French government, has realised, two years later en enquiry with a survey about research centres and periodicals. 167 responses from teams and 139 from periodicals, have enabled a better knowledge about researches contents and joining disciplines, and then, for periodicals to show in particular the weight of administrations in their management and low distribution.